IMPLEMENTATION OF A LOCAL CULTURE BASED SCIENTIFIC APPROACH TO IMPROVE YOUR CREATIVE THINKING SKILLS IN BASIC TEACHER EDUCATION STUDENTS - Ali Armadi; Sihabuddin Sihabuddin (Widyagogik, 2021)
The purpose of this research is to describe the increase in creative thinking skills in each student of the PGSD STKIP PGRI Sumenep Study Program through a scientific approach. The test results in the first cycle have scored above average, this is because the attention of students in lecturing activities given by the lecturer has been able to understand and understand the material given, so that the student's creative thinking ability has reached the target. The percentage of completeness that initially got 71% increased to 88%, while the observation of student creative thinking got 72% initially.increased in cycle II to 80%. The results of student creative thinking observations have increased.